2021
DOI: 10.7250/bjrbe.2021-16.543
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Settlement Behaviour of Soft Ground Under Wide Embankment

Abstract: An elastoplastic numerical model for calculating the consolidation settlement of wide embankment on soft ground is established using PLAXIS finite element software to investigate the settlement behaviour of soft ground under the wide embankment. The distribution rules are analysed and compared to narrow embankments, such as surface settlements of ground and embankment, lateral displacement of soft ground at the foot of embankment slope and excess pore pressure in soft ground. The influence rule of elastic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The width of the embankments can reach tens or even hundreds of meters. These wide and ultra-embankment projects are mainly distributed on multi-lane or even supermulti-lane expressways (e.g., Shuijing-Guanjingtou Expressway in Shenzhen, China, embankment width: 200 m), the railway station (e.g., Jinan West Passenger Station of Beijing-Shanghai High-speed Railway, embankment width: 200 m), airport runway, taxiway, apron (e.g., Shenzhen Airport, embankment width: 400 m), metro vehicle depot (e.g., Guangzhou Metro Vehicle Depot, embankment width: 52-72 m) [6,7] etc. For wide embankments, previous studies have shown that the maximum settlement of the embankment no longer occurs at the centerline of the embankment due to the shear displacement generated near the foot of the ramp, but transfers to two sides.…”
Section: Doi: 101002/adts202300905mentioning
confidence: 99%
See 2 more Smart Citations
“…The width of the embankments can reach tens or even hundreds of meters. These wide and ultra-embankment projects are mainly distributed on multi-lane or even supermulti-lane expressways (e.g., Shuijing-Guanjingtou Expressway in Shenzhen, China, embankment width: 200 m), the railway station (e.g., Jinan West Passenger Station of Beijing-Shanghai High-speed Railway, embankment width: 200 m), airport runway, taxiway, apron (e.g., Shenzhen Airport, embankment width: 400 m), metro vehicle depot (e.g., Guangzhou Metro Vehicle Depot, embankment width: 52-72 m) [6,7] etc. For wide embankments, previous studies have shown that the maximum settlement of the embankment no longer occurs at the centerline of the embankment due to the shear displacement generated near the foot of the ramp, but transfers to two sides.…”
Section: Doi: 101002/adts202300905mentioning
confidence: 99%
“…For wide embankments, previous studies have shown that the maximum settlement of the embankment no longer occurs at the centerline of the embankment due to the shear displacement generated near the foot of the ramp, but transfers to two sides. That is to say, the settlement of narrow embankment is V-shaped, however, the settlement of wide embankment is W-shaped, [6,[8][9][10][11] as shown in Figure 1. The result has been thoroughly verified by indoor geotechnical centrifugal model test, field observation, and numerical simulation.…”
Section: Doi: 101002/adts202300905mentioning
confidence: 99%
See 1 more Smart Citation
“…The differential settlement increases with increasing groundwater level and subgrade height [27]. The differential settlement creates a soil arching effect in the embankments [28], which is higher at the edge of the slope than at the centerline [29]. Aiming at the above-mentioned issue, this research is based on the road widening project of National Highway-120 (N-120), Sindh, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…al,(2013) 7 explained the improvement in reinforcement rigidity was explained.It leads to a decrease in lateral displacements but not settlements and increases the structures' stability.Chin et.al, (2016) 8 explained the effective ground treatment using prefabricated vertical drains and geogrids measured settlements more than the calculated settlements.Suresh et. al, (2020) 9 explainedthat the lateral pressures and deformation along the depth are analyzed in this paper.Fu et.al, (2021) 10 explained thata wide embankment has lower settlements than a narrow embankment. A wide embankment has more excess pore water pressure than a narrow embankment.Kommu et.…”
Section: Introductionmentioning
confidence: 99%